Pola POLA PENDIDIKAN DALAM PERSEPEKTIF PESANTREN - idhar idhar (PEDAGOGOS : Jurnal Pendidikan, 2019)
If judging specifically that the multi-dimensional kerisis that hit Indonesia sebernanya sourced from the decline of moral quality. When you see negative events involving students in Indonesia, such as brawls between students who never end, drugs, even cases of nasty video. This happens because the loss of moral values that faded due to lack of concern for school. Pesantren is an educator institution, not only educate the santri of religious knowledge, but also provide with the character that characteristic of a santri. It is not excessive when pesantren is said to be the source of character education to answer the nation's problems. Cases that many occur in students is due to lack of character education in students. The hallmark of pesantren and very difficult to imitate by other educational institutions is the strength of cultivation of morals. The label 'santri' was dzahir has been synonymous with piety, both individual and social. This is reasonable, because the habituation of morally appropriate applications have been ingrained in the education of boarding schools. Kyai as the central figure in it gives uswah and qudwah hasanah in moral education. Because the cultivation of morals more hit with deeds rather than juxtaposition of materials in the classroom, then moral education in boarding school very striking in the minds of the santrinya. It was precisely the one that inspired Kemendiknas to include elements of character education in schools, which were admittedly inspired by the moral education of pesantren. The purpose of education is to increase faith and piety and noble character in order to educate the nation's life, regulated by law (Article 31 paragraph 3) In this article explained that the purpose of education in Indonesia is aimed at increasing faith and piety and noble ahlak on students in reality as far away as fire from roast. The teaching system that schools give to their students is mostly oriented only to intellectual intelligence (intelligence), while the planting of character values on sisawa is very less. In this paper I discuss about the discussion about the pattern of education in pesantren, as well as the cultivation of values in studying